MEDIA ONLINE ISLAM DI MASYARAKAT MULTIKULTUR - ENI MARYANI; M. FAKHRUDI AKBAR (Communication, 2013)
This paper examined Indonesia’s Islamic online media and their consequences on the multicultural society. This study employed content analysis of 10 Islamic online media in Indonesia. The result of the study shows that 1) Representation as Islamic media was showed by the name of the website, the concept of the icon or specific terms, rubrics name, and alignments to the Islamic countries in the conflict against Israel and United States of America. 2) The packaging of the contents as Islamic media can be read from the tagline that underlined Islam the main issue, declaring the fighting for ‘the truth’ that is in line with Islam, and asserting the media as “Islamic struggle tool”. 3) Islamic online media in Indonesia had the potential to understand some Muslim views as a part of multicultural society; however, they also had the possibility to promote conflicts and to increase the escalation of conflicts in the multicultural society. This study suggests the significance of dialogue between the editors in the religion-based media about the role of media in the multicultural society. The need of media literacy for the journalists and readers of the Islamic-based media is also recommended.